2006
DOI: 10.2353/ajpath.2006.050801
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Discoidin Domain Receptor 1 Contributes to the Survival of Lung Fibroblast in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF), characterized by fibroblast proliferation and accumulation of extracellular matrix, including collagen, is a chronic progressive disorder that results in lung remodeling and fibrosis. However, the cellular mechanisms that may make fibroblasts resistant to apoptosis have not been completely elucidated. Discoidin domain receptor 1 (DDR1), a receptor tyrosine kinase whose ligand is collagen, is expressed in vivo and contributes in vitro to leukocyte differentiation and nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(61 reference statements)
0
20
0
2
Order By: Relevance
“…on May 10, 2018. by guest www.bloodjournal.org From MD), as previously reported. [10][11][12][13][14][15] Additionally, tyrosine phosphorylation of DDR1 and Shc recruitment were analyzed by Western blotting using mouse monoclonal antiphosphotyrosine IgGs (4G10; Upstate Biotechnology) or mouse monoclonal anti-Shc antibodies (R&D Systems, Minneapolis, MN), followed by sheep anti-mouse IgGs coupled with horseradish peroxidase (Amersham). The peroxidase activity was visualized using the enhanced chemiluminescence detection system (Amersham).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…on May 10, 2018. by guest www.bloodjournal.org From MD), as previously reported. [10][11][12][13][14][15] Additionally, tyrosine phosphorylation of DDR1 and Shc recruitment were analyzed by Western blotting using mouse monoclonal antiphosphotyrosine IgGs (4G10; Upstate Biotechnology) or mouse monoclonal anti-Shc antibodies (R&D Systems, Minneapolis, MN), followed by sheep anti-mouse IgGs coupled with horseradish peroxidase (Amersham). The peroxidase activity was visualized using the enhanced chemiluminescence detection system (Amersham).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…10 In addition, we have recently found that DDR1 conferred protection to the pulmonary fibroblasts from Fas ligand-induced apoptosis. 11 These findings led us to hypothesize that DDR1 might contribute to the prolonged survival of eosinophils in CSS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblasts cultured from IPF lungs possess a heritable profibrotic phenotype characterized by myofibroblastic differentiation (29) and increased collagen-1 (COL1) synthesis (36). Although epigenetic alterations are known to contribute (8,39), mechanisms driving the heritable profibrotic phenotype of IPF lung fibroblasts are poorly known.…”
mentioning
confidence: 99%
“…Recent attention has focused on ECM components and mesenchymal cell phenotypes as being critical to the development of fibrosis (1,2). The ECM is a highly dynamic complex that varies in composition according to its tissue localization and physiologic circumstances.…”
mentioning
confidence: 99%